Dynamics of Murabahah Disputes: Factor Analysis and Decisions of the Indonesian Religious Courts (2010-2024) - Perawati, Perawati; Mursal, Mursal; Fauzi, Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Purpose: This paper aims to examine the factors contributing to the resolution of Murabaha contract disputes in religious courts.Design/Method/Approach : This research uses content analysis, applying a qualitative approach with primary data obtained from Murabaha dispute resolution decisions in Indonesian Religious Courts from 2010 to 2024, accessible via the website https://bangunan3.mahkamahagung.go.id using the keyword 'Murabahah.' Secondary data is sourced from journals and books to supplement the research material.Findings: Based on the data obtained from the website https://bangunan3.mahkamahagung.go.id for the years 2010-2024, there are 220 decisions available. The majority of these decisions are related to breach of contract claims rather than actions against the law. The primary cause of breach of contract is the failure to fulfill or comply with agreed contractual obligations, while the cause of actions against the law involves disputes where the buyer or lender opposes the use of insurance or securities sold at auction.Originality/Values: The main contribution of this research is to describe the factors causing the resolution of murabahah contract disputes in religious courts from 2010 to 2024.